Physical–numerical parameters in turbulent simulations of natural convection on three-dimensional square plates - Verdério Júnior, Sílvio Aparecido (2022)
Purpose: This paper aims to study, experimentally validate and select the main physical and numerical parameters of influence in computational numerical simulations to evaluate mean heat flux by natural convection on square flat plates. Design/methodology/approach: Several numerical models were built to study the influence of physical and numerical parameters about the predictions of the natural convection heat transfer rates on the surface of a flat plate with aspect ratio = 1, in isothermal conditions, turbulent regime and using the free and open-source software OpenFOAM®. The studied parameters were: boundary conditions (using or not using wall functions in properties ε, κ, νt and ω), degree of mesh refinement, refinement layers and turbulence models [κ – ε and κ – ω Shear Stress Transport (SST)]. From the comparison of the values of the mean Nusselt number, obtained from numerical simulations and literature experimental results, the authors evaluated the precision of the studied parameters, validating and selecting the most appropriate to the analyzed problem situation. Findings: The validation and agreement of the numerical results could be proven with excellent precision from experimental references of the technical scientific literature. More refined meshes with refinement layers were not suitable for the studies developed. The κ – ε and κ – ω SST turbulence models, in meshes without refinement layers, proved to be equivalent. Whether or not to use wall functions in turbulent boundary conditions proved to be irrelevant as to the accuracy of results for the problem situation studied. Practical implications: Use of the physical and numerical parameters is studied and validated for various applications in natural convection heat transfer of technology and industry areas. Social implications: Use of free and open-source software as a research tool in the Computational Fluid Dynamics (CFD) area, especially in conditions without large financial resources or state-of-the-art infrastructure. Originality/value: To the best of the authors’ knowledge, this work is yet not available in existing literature.